Prognostic significance of microvessel density and other variables in Japanese and British patients with primary invasive breast cancer. - Kato, T; Steers, G; Campo, L; Roberts, H; Leek, R; Turley, H; Kimura, T; Kameoka, S; Nishikawa, T; Kobayashi, M; Harris, A; Gatter, K; et al. (2007)
The purpose of this study is to investigate the associations of microvessel density (MVD) and other pathological variables with survival, and whether they accounted for survival differences between Japanese and British patients. One hundred seventy-three Japanese and 184 British patients were included in the study. British patients were significantly older (56.3+/-11.4 years vs 52.5+/-12.9 years; P<0.01) and had smaller tumours (2.2+/-1.3 vs 2.7+/-1.8 cm; P<0.01), which were more frequently oestrogen receptor positive (78.8 vs 57.2%, P<0.01), had more grade III tumours (29.9 vs 21.4%, P=0.04) and more infiltrating lobular carcinomas (13.6 vs 4.0%, P<0.01) and a higher MVD compared with Japanese patients (57.9+/-19.8 vs 53.2+/-18.6; P=0.01). However, no difference in the prevalence of lymph-node metastasis was found between them (39.1 vs 37.5%, P=0.75). Younger British patients (age <50 years) had the highest MVD compared with Japanese and older British patients (P<0.01). Japanese patients were proportionately more likely to receive chemotherapy than endocrine therapy (P<0.01). British patients had a significantly worse relapse-free survival and overall survival compared with Japanese patients, after statistical adjustment for variables (hazard ratio=2.1, 2.4, P<0.01, P<0.01, respectively), especially, in T2 stage, low MVD and older subgroup (HR: 3.6, 5.0; 3.1, 3.3; 3.2, 3.9, respectively), but only in ER negative cases (P=0.04, P=0.01, respectively). The present study shows that MVD contributes to the Japanese-British disparity in breast cancer. However, the MVD variability did not explain the survival differences between Japanese and British patients.